The Role of Fiscal Policy in Encouraging the Adoption of Green Chemistry Technology in the Industrial Sector - Permana, Teguh; Puspitaningsih, Andriani (Science Tech Group, 2025)
This study examines the effectiveness of fiscal policy in promoting the adoption of green chemistry technology in Indonesia’s chemical industry sector using content analysis of 48 official secondary documents from 2018–2024. The analysed documents include regulations issued by the Minister of Finance, incentive realisation reports from the Directorate General of Taxes (DJP), investment data from BKPM, PROPER reports from the Ministry of Environment and Forestry (KLHK), sustainability reports of chemical companies listed on the Indonesia Stock Exchange (BEI), and international references from UNEP, OECD, and ICCA. The findings reveal that, despite the availability of various fiscal incentives (super deduction tax of up to 300%, tax holidays, and tax allowances), only 2.8% of the total incentives absorbed by the chemical sector in 2024 were actually directed toward green chemistry activities—significantly lagging behind Germany (31%) and South Korea (28%). The low uptake is primarily caused by the deferred nature of the incentives, convoluted and time-consuming application procedures (taking more than nine months), and the lack of clear technical definitions of green chemistry in existing regulations. These results are supported by pecking order financing theory (Myers & Majluf, 1984), prospect theory (Kahneman & Tversky, 1979), and the push-pull framework of environmental innovation (Horbach et al., 2012). The study recommends a paradigm shift in fiscal policy toward upfront instruments, namely refundable tax credits of 30–40%, VAT exemptions on bio-based raw materials, and direct grants; simplification of procedures into a one-stop service with a maximum approval time of four months; and revision of Minister of Finance Regulation (PMK) No. 153/2020 by including explicit technical definitions of green chemistry. These measures are expected to accelerate Indonesia’s chemical industry sector in achieving the Net Zero Emission target by 2060.